A Newly Identified Relief from the Tomb-Chapel of Mose at Saqqara - Orsenigo, Christian (Zeitschrift für ägyptische Sprache und Altertumskunde, 2013)
A photograph has recently been found among the records left by Victor Loret following his discovery in 1898 of the tomb-chapel of Mose at Saqqara, of a relief lying still in situ, that does not appear in the publication of the tomb by Gaballa. The relief, very probably part of a limestone wall, is decorated with an offering scene showing a man, accompanied by a little procession, censing and libating before the Apis-bull in a shrine. The paper retraces the path of the relief from the art gallery of Maurice Nahman to the current location of its remaining left hand portion at the Rosicrucian Egyptian Museum, San Jose.